Altered morphine glucuronide and bile acid disposition in patients with nonalcoholic steatohepatitis. Issue 4 (15th March 2015) - Ferslew, BC; Johnston, CK; Tsakalozou, E; Bridges, AS; Paine, MF; Jia, W; Stewart, PW; Barritt, AS; Brouwer, KLR
<x xml:space="preserve">Abstract</x> The functional impact of altered drug transport protein expression on the systemic pharmacokinetics of morphine, hepatically derived morphine glucuronide (morphine‐3‐ and morphine‐6‐glucuronide), and fasting bile acids was evaluated in patients with biopsy‐confirmed nonalcoholic steatohepatitis (NASH) compared to healthy subjects. The maximum concentration (Cmax) and area under the concentration‐time curve (AUC0‐last) of morphine glucuronide in serum were increased in NASH patients (343 vs. 225 nM and 58.8 vs. 37.2 µM*min, respectively; P ≤ 0.005); morphine pharmacokinetics did not differ between groups. Linear regression analyses detected an association of NASH severity with increased morphine glucuronide Cmax and AUC0‐last (P < 0.001). Fasting serum glycocholate, taurocholate, and total bile acid concentrations were associated with NASH severity (P < 0.006). Increased hepatic basolateral efflux of morphine glucuronide and bile acids is consistent with altered hepatic transport protein expression in patients with NASH and may partially explain differences in efficacy and/or toxicity of some highly transported anionic drugs/metabolites in this patient population.